JAZZ IN TOTALITARIAN SYSTEMS (NAZIGERMANY AND FORMER USSR): THE LIFE OF THE TRUMPET PLAYER EDDIE ROSNER - Elisabeth Kolleritsch (European Scientific Journal, ESJ, 2015)
This cultural-political investigation about German and Russian jazz history before, during and after World War II is showing the life of the trumpet player Eddie Rosner, born 1910 in Berlin to a Polish-Jewish family. 1930 to 1933 member of the then famous German jazzband, Weintraubs Syncopators“, he tested 1933 in the United States the emigration possibilities. Finally he moved to Warsaw where he fled 1939 to the Russian-occupied city of Lviv (today Ukraine). After an engagement in Minsk he was appointed to lead the best-paid jazz band in the USSR. He played for Stalin in Sotchi, toured the whole Soviet Union and recorded a number of titles. During an attempt to return to Berlin without visa 1946 he was arrested and sent without trial into labour camps in Sibiria. After his release 1955 he settled in Moscow forming a large symphonic jazz orchestra. He was allowed to leave Moscow eventually in 1973 but all treaties for recordings were cancelled, his fortune was confiscated, his name extinguished. Before his death 1976 he had to make a living on a small pension in Berlin. His life shows how is working “political protection” in totalitarian systems. To make a research with serious results about him is not easy as source materials are spread mainly in Russia, Poland and Germany and have to be collected there before investigation and evaluation.